An Individually Controlled Multitined Expandable Electrode Using Active Cannula‐Based Shape Morphing for On‐Demand Conformal Radiofrequency Ablation Lesions. (1st May 2022) - Chai, Zhiping; Lyu, Liangxiong; Pu, Menghao; Chen, Xianwen; Zhu, Jiaqi; Liang, Huageng; Ding, Han; Wu, Zhigang
Abstract : Being minimally invasive and highly effective, radiofrequency ablation (RFA) is widely used for small‐sized malignant tumor treatment. However, in clinical practice, a large number of tumors are found in irregular shape, while the current RFA devices are hard to control the morphologic appearance of RFA lesions on demand, which usually ends up with unnecessarily excessive tissue ablation and subsequently often brings irreversible damage to the organs' functions. Herein, active cannulas for each of the individually controlled subelectrodes to achieve an on‐demand shape morphing and thus conformal RFA lesion are introduced. The target shape as well as the length of inserted subelectrodes can be precisely controlled by tuning the active stylets and cannulas. What's more, owing to independent movement and energy control of each subelectrodes, the electrode is shown to be not only efficient enough to accomplish accurate trajectory control to target tissue in a single insertion, but also adaptive enough to ablate target tissues with diverse morphologic appearances and locations. On‐demand conformal ablation of target tissue is demonstrated as well under the guidance of ultrasound imaging with the device. Potentially, the RFA electrode is a promising minimally invasive treatment of malignant tumors in future clinical practice. An interactive preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.164019293.38729522 . Abstract : An individual controlled multitined expandable electrode is presented here for on‐demand conformal ablation of target tissues. The individually controlled subelectrodes' shape can be morphed by tuning the relative position of precurved stylets and stiff cannulas. With rational energy input and three subelectrodes, the electrode can achieve 3D on‐demand conformal ablation efficiently.